Effect of botanically diverse pastures on the milk fatty acid profiles in New Zealand dairy cows - Ström, Gunilla (SLU/Dept. of Animal Nutrition and Management (until 231231), 2012)
Botanically diverse pastures are commonly used in New Zealand to reduce the ruminant environmental impact by reducing the methane production from the rumen digestion. In order to evaluate the effects diverse pasture species have on the milk fatty acid profile seventy-two lactating Friesian-Jersey crossbred dairy cows were used in a randomised block design with two replicates of six treatments. Six different pasture mixtures were fed at a daily allowance of approximately 15 kg DM/cow/day. The mixtures were categorised as either a simple or a diverse pasture. The simple mixtures all contained white clover with the addition of either a standard diploid perennial ryegrass (RG), a diploid high sugar ryegrass (HS) or tall fescue (TF). The three diverse mixtures included each of the simple mixtures with the addition of either chicory, plantain, prairie grass and red clover (RGD), chicory, plantain and big trefoil (HSD), or chicory, plantain, prairie grass and lucerne (TFD). Milk samples were collected and the fatty acid profile was analysed using Fatty Acids Methyl Esters (FAME) analysis. The proportion (g/100g of milk fat fatty acids) of linoleic and linolenic acid increased while the proportion of cis-9, trans-11 C18:2 (CLA) decreased in milk from cows grazing the diverse pastures compared to cows fed the simple pastures. These changes were probably associated with a shift in the rumen microbial population or rumen metabolic routes caused by several secondary metabolites present in some plants, e.g. herbs and legumes. As a consequence the lipolysis and biohydrogenation decreased, resulting in an increased rumen outflow of linoleic and linolenic acid. These assumptions are based on the reported effects of secondary metabolites on rumen methanogenesis. The results of this study suggest that it is possible to change the milk fatty acid profile through inclusion of diverse plant species in the pastures which provides opportunities to change the fatty acid composition to become more beneficial from a human health perspective.